2021
DOI: 10.1093/femsec/fiab034
|View full text |Cite
|
Sign up to set email alerts
|

Soil microbial communities influencing organic phosphorus mineralization in a coastal dune chronosequence in New Zealand

Abstract: The Haast chronosequence in New Zealand is a ∼6500-year dune formation series, characterized by rapid podzol development, phosphorus (P) depletion, and a decline in aboveground biomass. We examined bacterial and fungal community composition within mineral soil fractions using amplicon-based high-throughput sequencing (Illumina MiSeq). We targeted bacterial non-specific acid (class A, phoN/phoC) and alkaline (phoD) phosphomonoesterase genes and quantified specific genes and transcripts using real-time PCR. Soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 83 publications
2
6
2
Order By: Relevance
“…This enrichment was reflected in a depletion of other phyla (e.g., Mortirellomycota and Rozellomycota) and an overall decrease in fungal richness in both organic and mineral soil horizons (Figure S2). Similar results have been observed in the Haast chronosequence (Gaiero et al, 2021), where Ascomycota also dominated with dune age. Ascomycota are reported to harbour genomic traits that are associated with competitive abilities (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…This enrichment was reflected in a depletion of other phyla (e.g., Mortirellomycota and Rozellomycota) and an overall decrease in fungal richness in both organic and mineral soil horizons (Figure S2). Similar results have been observed in the Haast chronosequence (Gaiero et al, 2021), where Ascomycota also dominated with dune age. Ascomycota are reported to harbour genomic traits that are associated with competitive abilities (e.g.…”
Section: Discussionsupporting
confidence: 88%
“…Acidobacteria and Alphaproteobacteria were the predominant contributors in all nutrient cycling combinations. Together with the Actinobacteria , which showed the second highest association with C in our study, all of these groups are known from the literature to be involved in the C cycle ( 100 , 102 ), N cycle ( 90 ), and P cycle ( 12 , 15 ). We have also shown the functional potential of these groups for other nutrient combinations, including CN, CP, NP, and CNP.…”
Section: Discussionsupporting
confidence: 54%
“…A few examples include carbon-fixing Actinobacteria ( 9 , 10 ), nitrogen-fixing Azotobacter ( 9 , 10 ), and phosphate-solubilizing Acidobacteria ( 11 , 12 ). Likewise, Penicillium , Aspergillus , and Trichoderma are free-living fungi and known for being actively involved in the decomposition of soil organic compounds (C cycle), nitrification (N cycle), and P solubilization (P cycle), respectively ( 13 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Both Olson (1958) and Lichter (1998b) found that soil pH decreased from a nearshore peak between 7 and 8 to a low between 4 and 5 during the first 1,000 years of soil development. Other dune systems worldwide show a decrease in pH with time, but the magnitude of change and range varies (Nelson et al, 2020;Pollmann et al, 2020;Gaiero et al, 2021). Similarly, Lichter (1998a) at Wilderness State Park in lower peninsula of Michigan found that soil carbon and nitrogen asymptotically peaked between 500 and 1,000 years, respectively, at 40 and 2.3 mg/ha.…”
Section: Discussionmentioning
confidence: 97%